1998
DOI: 10.1007/bf02784036
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bone resorption is dependent on physiological concentrations of zinc

Abstract: The addition of physiological concentrations of zinc (25-200 (microg/dL) to Dulbecco's Modified Eagle's Medium containing tibiae from 19-d chick embryos resulted in a concentration-dependent increase in tibial content of tartrate-resistant acid phosphatase (TRAP) and an increase in bone resorption, as measured by tibial calcium release. This increase in bone resorption was additive to the resorptive effect resulting from the addition of 10(-9)-10(-7) M parathyroid hormone (PTH), but was not additive to similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Zinc is essential in the process of skeletal development, 1–50 μM zinc has been shown to inhibit osteoblast apoptosis and promote the proliferation and differentiation of osteoblasts, 98 and adding zinc (25–200 mg/dl) to the cultured chicken embryo tibia has been demonstrated to lead to a concentration‐dependent increase in tibial ALP activity and an increase in the level of bone formation, 99 physiological concentrations of zinc (25–200 mg/dl) have also been shown to increase bone resorption in tibia of chicken embryos. 100 Similarly, the effect of zinc on Ca 2+ in osteoblast‐related cells has not been exhibited, but it has been demonstrated that 10–30 μM zinc inhibited the increase in Ca 2+ concentration in BMMs induced by RANKL, and 30–100 μm zinc inhibited the CaN activity of BMMs. 101 …”
Section: Diverse Ca 2+ /Can/nfat Signalling Pathway Modulating Compounds Which Regulate Osteogenic Differentiationmentioning
confidence: 99%
“…Zinc is essential in the process of skeletal development, 1–50 μM zinc has been shown to inhibit osteoblast apoptosis and promote the proliferation and differentiation of osteoblasts, 98 and adding zinc (25–200 mg/dl) to the cultured chicken embryo tibia has been demonstrated to lead to a concentration‐dependent increase in tibial ALP activity and an increase in the level of bone formation, 99 physiological concentrations of zinc (25–200 mg/dl) have also been shown to increase bone resorption in tibia of chicken embryos. 100 Similarly, the effect of zinc on Ca 2+ in osteoblast‐related cells has not been exhibited, but it has been demonstrated that 10–30 μM zinc inhibited the increase in Ca 2+ concentration in BMMs induced by RANKL, and 30–100 μm zinc inhibited the CaN activity of BMMs. 101 …”
Section: Diverse Ca 2+ /Can/nfat Signalling Pathway Modulating Compounds Which Regulate Osteogenic Differentiationmentioning
confidence: 99%